Proving Reachability Using FShell - (Competition Contribution). - Holzer, A; Kroening, D; Schallhart, C; Tautschnig, M; Veith, H (Springer, 2012)
FShell is an automated white-box test-input generator for C programs, computing test data with respect to user-specified code coverage criteria. The pillars of FShell are the declarative specification language FQL (FShell Query Language), an efficient back end for computing test data, and a mathematical framework to reason about coverage criteria. To solve the reachability problem posed in SV-COMP we specify coverage of ERROR labels. As back end, FShell uses bounded model checking, building upon components of CBMC and leveraging the power of SAT solvers for efficient enumeration of a full test suite. © 2012 Springer-Verlag Berlin Heidelberg.